Early tumor shrinkage as a predictor of favorable outcomes in patients with advanced pancreatic cancer treated with FOLFIRINOX - Kaga, Yasuhiro; Sunakawa, Yu; Kubota, Yutaro; Tagawa, Teppei; Yamamoto, Taikan; Ikusue, Toshikazu; Uto, Yu; Miyashita, Kouichirou; Toshima, Hirokazu; Kobayashi, Kouji; Hisamatsu, Atsushi; Ichikawa, Wataru; et al. (Oncotarget, 2016)
There are several reports on the correlation between early tumor shrinkage (ETS) or depth of response (DpR) and survival in chemotherapies for colorectal cancer; however, few studies have investigated it in pancreatic cancer. We therefore investigated whether the ETS will predict outcomes in 59 patients with advanced pancreatic cancer treated with FOLFIRINOX therapy. The association of ETS with progression-free survival (PFS) and overall survival (OS) was evaluated but also we addressed to the correlation between outcomes and DpR. ETS was defined as a reduction ≥ 20% of target lesions' diameters measured at 6 to 8 weeks from treatment start. DpR was percentage of maximal tumor shrinkage observed at the nadir diameter compared with baseline. Among 47 evaluable patients for the ETS, 12 (25.5%) patients experienced ETS. The ETS was significantly associated with better PFS (9.0 vs. 4.2 months) as well as OS (24.0 vs. 9.1 months); moreover, the association had a statistically significance for PFS but a strong trend for OS in multivariate analysis. The DpR was statistically significantly but weakly associated with OS. In conclusion, this is the first report that the early response to chemotherapy may predict favorable outcomes in patients with advanced pancreatic cancer treated with FOLFIRINOX therapy.